Labour law for TOS and HITs? reflections on the potential for applying 'labour law analogies' to crowdworkers, focusing on employee representation. (1st December 2018) - Christina Hiessl
Abstract : A growing number of people are performing work tasks via online platforms, referred to under various designations such as 'Human Intelligence Tasks' (HITs), under conditions set out not in an employment contract but through the standardised Terms of Service (TOS) of their contract partner. This article argues that, in spite of increasing evidence of precarious working conditions and circumvention of labour law and social protection standards in 'turking'-style work environments, attempts to classify these forms of crowdwork as employment relationships are of limited practical use and benefit for those working in the industry. Instead, departing from much-debated concepts of a 'purposive' approach to labour law, it makes the case for a differential analysis of the aims of diverse elements of labour law and a consideration of whether, and to what degree, these can be instrumentalised for dealing with a contractual relationship that, notwithstanding socio-economic similarities, is fundamentally different from the employment relationship for which that law was developed, in several respects. It discusses the merits of rules on workplace employee representation and explores options for operationalising these for crowdworkers. For this purpose, it considers forms of collective organisation of crowdworkers via various networks as they already exist and are emerging in practice to question whether it is or should be reasonable for crowdworkers to be legally entitled to rights analogous to the workplace representation bodies such as works councils, which would entitle them to rights ranging from information and consultation to co-determination as well as veto rights on specific issues.